PENERAPAN METODE FIFO DAN FEFO DALAM SISTEM MANAJEMEN OBAT KLINIK APOTEK XYZ: APPLICATION OF FIFO AND FEFO METHODS IN THE PHARMACY CLINIC DRUG MANAGEMENT SYSTEM XYZ - Muhammad fahmi Rosyadi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Effective drug stock management is a vital element for maintaining service continuity in pharmacies and clinics. Inaccuracies in inventory control risk significant financial losses and jeopardize patient safety due to the potential use of expired drugs. The XYZ Pharmacy Clinic currently relies on a manual recording system, a process prone to human error and inefficiency, particularly in tracking and distribution. This research addresses this gap by developing a web-based drug stock management information system integrating FIFO (First In First Out) and FEFO (First Expired First Out) methodologies, enhanced with real-time stock analysis features to support dynamic decision-making. The Research and Development (R&D) method was employed. Data was gathered through two-week field observation of three pharmacy staff members, structured interviews, and documentation studies. A significant technical enhancement was performed: a database migration from MySQL to PostgreSQL using DBConvert, validated through pgAdmin 4, to improve backend performance, scalability, and data integrity. Black Box Testing across 5 scenarios confirmed all system functions operated as expected. Performance testing using Google Lighthouse yielded an LCP (Largest Contentful Paint) value of 0.97 seconds, classified as excellent by Google Web Vitals standards (<2.5 seconds). The system has proven to improve stock recording efficiency, provide automated expiry notifications, and present inventory data through clear visualizations.